A Protective Role of Tumor Necrosis Factor Superfamily-15 in Intracerebral Hemorrhage-Induced Secondary Brain Injury. (October 2021) - Yang, Gui-Li; Wang, Shizhao; Zhang, Shu; Liu, Ye; Liu, Xiao; Wang, Dong; Wei, Huijie; Xiong, Jianhua; Zhang, Zhi-Song; Wang, Zengguang; Li, Lu-Yuan; Zhang, Jianning
Destabilization of blood vessels by the activities of vascular endothelial growth factor (VEGF) and matrix metalloproteinases (MMPs) following intracerebral hemorrhage (ICH) has been considered the main causes of aggravated secondary brain injury. Here, we show that tumor necrosis factor superfamily-15 (TNFSF15; also known as vascular endothelial growth inhibitor), an inhibitor of VEGF-induced vascular hyper-permeability, when overexpressed in transgenic mice, exhibits a neuroprotective function post-ICH. In this study, we set-up a collagenase-induced ICH model with TNFSF15-transgenic mice and their transgene-negative littermates. We observed less lesion volume and neural function perturbations, together with less severe secondary injuries in the acute phase that are associated with brain edema and inflammation, including vascular permeability, oxidative stress, microglia/macrophage activation and neutrophil infiltration, and neuron degeneration, in the TNFSF15 group compared with the littermate group. Additionally, we show that there is an inhibition of VEGF-induced elevation of MMP-9 in the perihematomal blood vessels of the TNFSF15 mice following ICH, concomitant with enhanced pericyte coverage of the perihematomal blood vessels. These findings are consistent with the view that TNFSF15 may have a potential as a therapeutic agent for the treatment of secondary injuries in the early phase of ICH.